Predictors, rates, and trends of opioid use disorder among patients hospitalized with chronic pancreatitis - Adejumo, Adeyinka Charles (Ann Gastroenterol, 2021)
BACKGROUND: Patients with chronic pancreatitis (CP) suffer from pain and receive increased opioid prescriptions with a high risk of opioid use disorder (OUD). We studied the predictors, trends and outcomes of OUD among patients hospitalized with CP. METHODS: Records with CP (with/without OUD) were extracted from the Nationwide Inpatient Sample (NIS) 2012-2014, and the association of OUD with the burden of CP was calculated. We then charted the trends of OUD and its interaction with concomitant CP from NIS 2007-2014 (SAS 9.4). RESULTS: In the period 2012-2014, 4349 (4.99%) of the 87,068 CP patients had concomitant OUD, with higher risk among patients who were young, females, white vs. Hispanics, and individuals with chronic back pain, arthritis, non-opioid substance use, mental health disorders, and those hospitalized in urban centers. OUD was associated with a longer hospital stay (6.9 vs. 6.5 days, P=0.0015) but no significant difference in charges ($47,151 vs. $49,017, P=0.0598) or mortality (1.64% vs. 0.74%, P=0.0506). From 2007-2014, the average yearly rate of OUD was 174 cases per 10,000 hospitalizations (174/10,000), almost 3 times higher among CP vs. non-CP (479/10,000 vs. 173/10,000, P<0.001), and it increased from 2007 to 2014 (135/10,000 to 216/10,000, P<0.001). The yearly increase was 2.7 times higher among patients with CP vs. non-CP (29.9/10,000 vs. 11.3/10,000 hospitalizations/year, P<0.001). CONCLUSIONS: CP is associated with higher rates and trends of OUD. Patients with CP at high risk of OUD may benefit from alternate analgesic regimens or surveillance for OUD when they are prescribed opioids.